2011
DOI: 10.4049/jimmunol.1002735
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Critical Role of Intracellular Osteopontin in Antifungal Innate Immune Responses

Abstract: We found that absence of osteopontin (OPN) in immunocompromised Rag2−/− mice, which lack T and B cells, made the mice extremely susceptible to an opportunistic fungus Pneumocystis, although immunocompetent OPN-deficient mice could clear Pneumocystis as well as wild-type mice. OPN has been studied as an extracellular protein, and the role of an intracellular isoform of osteopontin (iOPN) is still largely unknown. Here, we elucidated the mechanism by which iOPN was involved in anti-fungal innate immunity. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 31 publications
0
65
1
1
Order By: Relevance
“…iOPN was previously established as a proinflammatory molecule, but we found in this study that iOPN served as a negative regulator of inflammatory responses in concert with adaptive immune cells. iOPN faithfully behaves as a proinflammatory molecule when hosts are comprised of the innate immune system alone (24). However, we have shown that iOPN could behave as an anti-inflammatory molecule when the adaptive immune system is present.…”
Section: Discussionmentioning
confidence: 75%
“…iOPN was previously established as a proinflammatory molecule, but we found in this study that iOPN served as a negative regulator of inflammatory responses in concert with adaptive immune cells. iOPN faithfully behaves as a proinflammatory molecule when hosts are comprised of the innate immune system alone (24). However, we have shown that iOPN could behave as an anti-inflammatory molecule when the adaptive immune system is present.…”
Section: Discussionmentioning
confidence: 75%
“…These findings suggest that in DENinduced HCC, production of cytokines by resident liver macrophages is mainly via the TLR4/MyD88 signaling. Previous studies have suggested that iOPN might perform as one of the intracellular regulators of TLR2/TLR9 signaling to balance the cytokine milieu (16,21). In plasmacytoid dendritic cells, shortly after TLR9 engagement, iOPN interacted with MyD88 and enhanced interferon-a production (16).…”
Section: Discussionmentioning
confidence: 99%
“…In plasmacytoid dendritic cells, shortly after TLR9 engagement, iOPN interacted with MyD88 and enhanced interferon-a production (16). In antifungal innate immunity, iOPN acted as an adaptor molecule in TLR2 and dectin-1 signaling pathways and increased zymosan-induced cytokine production such as IL1b and IL10 (21). Following TLR stimulation in macrophages, iOPN was induced in vivo and in vitro and negatively regulated interferon-b production in murine macrophages (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that osteopontin, which participates in innate immune responses to other infectious agents, is highly upregulated in AMs of Pneumocystis-infected immunosuppressed rats (37). Recently, Inoue et al have shown that the intracellular isoform of osteopontin is involved as an adaptor molecule in the collaboration of Toll-like receptor 2, dectin 1, and mannose receptor following interaction of Pneumocystis with AMs (129). Additional studies demonstrated a role for intracellular osteopontin in enhancement of phagocytosis and clearance of Pneumocystis (129).…”
Section: Macrophagesmentioning
confidence: 99%